Rationale and Design of the PAIRED Trial: Partnered Dance Aerobic Exercise as a Neuroprotective, Motor, and Cognitive Intervention in Parkinson's Disease - Hackney, Madeleine E.; Bay, Allison A.; Jackson, Jordan M.; Nocera, Joe R.; Krishnamurthy, Venkatagiri; Crosson, Bruce; Evatt, Marian L.; Langley, Jason; Cui, Xiangqin; McKay, J. Lucas; Huddleston, Daniel E. (Frontiers in Neurology, 2020)
Parkinson’s disease (PD), an intractable condition impairing motor and cognitive function, is imperfectly treated by drugs and surgery. Two priority issues for many people with PD are OFF-time and cognitive impairment. Even under best medical management, three-fourths of people with PD experience “OFF-time” related to medication-related motor fluctuations, which severely impacts both quality of life and cognition. Cognitive deficits are found even in newly diagnosed people with PD and are often intractable. Our data suggests that partnered dance-aerobic exercise (PDAE) reduces OFF-time on the Movement Disorders Society Unified Parkinson Disease Rating Scale-IV, MDS-UPDRS-IV and ameliorates other disease features motivate the PAIRED trial. PDAE provides AE during an improvisational, cognitively engaging rehabilitative physical activity. Although exercise benefits motor and cognitive symptoms and may be neuroprotective for PD, studies using robust biomarkers of neuroprotection in humans are rare. We propose to perform a randomized, controlled trial in individuals with diagnosed mild- moderate PD to compare the efficacy of PDAE versus walking aerobic exercise (WALK) for OFF-time, cognition, and neuroprotection. We will assess neuroprotection with neuromelanin-sensitive MRI (NM-MRI) and iron-sensitive (R2*) MRI sequences to quantify neuromelanin loss and iron accumulation in substantia nigra pars compacta (SNc). We will use these biomarkers, neuromelanin loss and iron accumulation, as tools to chart the course of neurodegeneration in patients with PD who have undergone long-term (16 months) intervention. We will randomly assign 102 individuals with mild-moderate PD to 16 months of PDAE or WALK. The 16-month intervention period will consist of Training (3 months of biweekly sessions) and Maintenance (13 months of weekly sessions) phases. We will assess participants at baseline, 3 months (immediately post-Training), and 16 months (immediately post-Maintenance) for OFF-time and behaviorally and physiologically measured cognition. We will acquire NM-MRI and R2* imaging data at baseline and 16 months to assess neuroprotection. We will: 1. examine effects of Training and Maintenance phases of PDAE vs. WALK on OFF-time; 2. compare PDAE vs WALK at 3 and 16 months on behavioral and fMRI measures of spatial cognition; and 3. compare PDAE vs. WALK for effects on rates of neurodegeneration.